Makna Kerja sebagai Ibadah pada Karyawan Muslim di Era Kapitalisme Modern - Khusnul Lailia; Abdul Aziz Nugraha Pratama (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the concept of work from an Islamic perspective through the maqashid al-sharia approach, the concept of falah, and the Islamic work ethic as a foundation for navigating the dynamics of the modern workplace. The study employs a qualitative method using a literature review approach through the analysis of various relevant journals, books, and literature. The results indicate that Islam views work not merely as an economic activity but also as a form of worship and a moral responsibility of humanity as stewards on Earth. The concept of maqashid syariah positions work as a means to safeguard religion, life, intellect, lineage, and wealth, while the concept of falah emphasizes a balanced pursuit of worldly and afterlife well-being. The implementation of the Islamic work ethic is reflected through the values of discipline, trustworthiness, honesty, professionalism, justice, and humane workplace relationships. Furthermore, Islamic spirituality and organizational culture play a crucial role in helping Muslim workers cope with the pressures of productivity, individualism, and materialism in the modern era. Thus, the Islamic perspective offers a work paradigm that is not only oriented toward productivity and material gain but also toward blessings, life balance, and social welfare.